2006
DOI: 10.5694/j.1326-5377.2006.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and cost of adverse events in Victorian hospitals 2003–04

Abstract: Objectives: To determine the incidence of adverse events in patients admitted in the year 2003–04 to selected Victorian hospitals; to identify the main hospital‐acquired diagnoses; and to estimate the cost of these complications to the Victorian and Australian health system. Design: The patient‐level costing dataset for major Victorian public hospitals, 1 July 2003 – 30 June 2004, was analysed for adverse events by identifying C‐prefixed diagnosis codes denoting complications, preventable or otherwise, arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 23 publications
3
105
1
2
Order By: Relevance
“…The three studies we excluded because of an insufficient number of patient records evaluated, when combined, 1607 records, amounting to 2% of all records included in this systematic review (more than 74 000 records). The two excluded studies that used a computer-assisted approach7 8 reported incidences of adverse events that were slightly lower (8.3% and 6.9%) than the median incidence of the studies included in the present review. This approach is much less time-consuming than the retrospective record review, but a drawback is that it cannot make judgements on causation or preventability.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The three studies we excluded because of an insufficient number of patient records evaluated, when combined, 1607 records, amounting to 2% of all records included in this systematic review (more than 74 000 records). The two excluded studies that used a computer-assisted approach7 8 reported incidences of adverse events that were slightly lower (8.3% and 6.9%) than the median incidence of the studies included in the present review. This approach is much less time-consuming than the retrospective record review, but a drawback is that it cannot make judgements on causation or preventability.…”
Section: Discussionmentioning
confidence: 81%
“…Of the remaining 29 studies, another 17 were excluded after reviewing the full article. Three of these studies applied a different definition of an AE; one study used an observational approach and recorded only errors without linking them to outcomes;6 the other two studies used a computer-assisted approach to screen a large number of patient records for certain codes denoting complications 7 8. Three studies were excluded because of an insufficient number of patient records; one of these studies used retrospective record review;9 the other studies would otherwise have been excluded due to methodological designs that differed from the large record review studies 10 11.…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events are estimated to cost the Australian healthcare system $2 billion per annum3 in direct costs alone.…”
Section: Introductionmentioning
confidence: 99%
“…Mary E Brindle, 1 Derek J Roberts, 2 Oluwatomilayo Daodu, 1 Alex Bernard Haynes, 3,4 Christy Cauley, 3 Elijah Dixon, 5 Claude La Flamme, 6 Paul Bain, 7 Strengths and limitations of this study ► The aims and objectives of the study have been established by a group of international stakeholders in surgical quality and safety representing relevant surgical specialties. ► Results of this meta-analysis need to be interpreted alongside that of landmark trials.…”
Section: Deriving Literature-based Benchmarks For Surgical Complicatimentioning
confidence: 99%
“…Despite the fact that the data have not been thoroughly explored, USA, the UK, Canada, Australia and New Zealand have all identified high rates of medical errors contributing to patient deaths and morbidity. [3][4][5][6][7] Surgery plays a central role in the national burden of medical care-related morbidity. 8 This is because surgery is a resource-intensive, often high-risk therapy within which there is ample opportunity for error.…”
Section: Introductionmentioning
confidence: 99%